Dugbe virus ovarian tumour domain interferes with ubiquitin/ISG15-regulated innate immune cell signalling - Bakshi, S. (Society for General Microbiology, 2013)
The ovarian tumour (OTU) domain of the nairovirus L protein has been shown to remove ubiquitin and interferon-stimulated gene 15 protein (ISG15) from host cell proteins, which is expected to have multiple effects on cell signalling pathways. We have confirmed that the OTU domain from the L protein of the apathogenic nairovirus Dugbe virus has deubiquitinating and deISGylating activity and shown that, when expressed in cells, it is highly effective at blocking the TNF-α/NF-κB and interferon/JAK/STAT signalling pathways even at low doses. Point mutations of the catalytic site of the OTU [C40A, H151A and a double mutant] both abolished the ability of the OTU domain to deubiquitinate and deISGylate proteins and greatly reduced its effect on cell signalling pathways, confirming that it is this enzymic activity that is responsible for blocking the two signalling pathways. Expression of the inactive mutants at high levels could still block signalling, suggesting that the viral OTU can still bind to its substrate even when mutated at its catalytic site. The nairovirus L protein is a very large protein that is normally confined to the cytoplasm, where the virus replicates. When the OTU domain was prevented from entering the nucleus by expressing it as part of the N-terminal 205 kDa of the viral L protein, it continued to block type I interferon signalling, but no longer blocked the TNF-α-induced activation of NF-κB.